2020
DOI: 10.18632/aging.104058
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the fatal toxic effects associated with CD19 CAR-T cell therapy

Abstract: To determine the incidence, spectrum, timing, and clinical features of CD19 Chimeric antigen receptor (CAR-T) cell therapy-associated fatal toxic effects. We initiated a comprehensive analysis. First, we retrospectively queried the real-world data from a World Health Organization (WHO) pharmacovigilance database (Vigilyze). Furthermore, we performed a meta-analysis of published trials of CD19 CAR-T cell therapy. From screening the WHO database, we identified 1200 patients: 499 received Kymriah therapy, and 701… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Among them, the number of reports following tisagenlecleucel, axi-cel, liso-cel, and KTE-X19 were 893 (58.83%), and 562 (37.02%), 25 (1.65%), 38 (2.50%), respectively (Table 1). Likewise, gastrointestinal disorders were also reported in previous real-world study (25). Cai et al reported the rates of GIAEs were 13% and 10% following tisagenlecleucel and axicel infusion, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…Among them, the number of reports following tisagenlecleucel, axi-cel, liso-cel, and KTE-X19 were 893 (58.83%), and 562 (37.02%), 25 (1.65%), 38 (2.50%), respectively (Table 1). Likewise, gastrointestinal disorders were also reported in previous real-world study (25). Cai et al reported the rates of GIAEs were 13% and 10% following tisagenlecleucel and axicel infusion, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…Ever since the amazing results obtained by Coley’s Toxin, adverse effects (AEs) have been a serious issue with immunotherapy. By turning off regulatory mechanisms, the immune system can go into overdrive causing issues such as Cytokine Release Syndrome (CRS)—an inflammatory process that can cause high fever and sometimes organ failure ( 18 , 50 , 54 ). This is part of what is sometimes referred to as a “cytokine storm” reaction to a pathogen or in the present discussion, CAR-T or checkpoint inhibition therapy, where a marked dysregulation of cytokine production can lead to fatal outcomes ( 18 ).…”
Section: A Brief History Of Cancer Immunotherapymentioning
confidence: 99%
“…In blood tumors, despite the relative specificity of the CD19 receptor, bone marrow aplasia can occur resulting in death or requiring stem cells transplantation [ 29 , 30 ]. Despite the developed treatment in the form of tocilizumab (an anti-IL-6 receptor antibody), there are cases where the patient dies regardless of its application [ 31 , 32 ]. Besides the mentioned tocilizumab, there is also treatment with siltuximab (anti-IL-6 antibody) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%